The Effect of Distance Learning Practicum based on PhET Interactive Simulations on Science Process Skills of Secondary School Students - Nur Efendi; Septi Budi Sartika (JURNAL PENDIDIKAN SAINS (JPS), 2021)
The condition of the covid-19 pandemic makes face-to-face learning become distance learning, learning activities from home are no exception to practicum learning. Alternative solutions using PhET Interactive Simulations. The research aims to describe the influence and great influence of PhET Interactive Simulations-based distance practicum learning on the science process skills of junior high school students. The research method uses quasi-experimentation with matching pre-test post-test control group design. The research population is grade VIII students of SMP Sepuluh Nopember Sidoarjo with a sample of 2 grade VIII, namely VIII H as an experimental class and VIII F as a control class of 40 students each. Research instruments use science process skills tests with 7 indicators namely formulating problems, formulating hypotheses, identifying variables and operational definitions of variables, assembling tools and materials, presenting data, conducting data analysis, and concluding. The results showed there is a huge influence between distance learning practicum based on PhET interactive simulations on the science process skills of secondary school students in natural science subjects. Further research increases the number of research variables, in addition to science process skills as well as understanding of student concepts to science, and so on.